Three new HLA‐C alleles (HLA‐C*14:02:13, HLA‐C*15:72 and HLA‐C*15:74) in Saudi bone marrow donors. (4th August 2015) - Fakhoury, H. A.; Jawdat, D.; Alaskar, A. S.; Al Jumah, M.; Cereb, N.; Hajeer, A. H.
Summary Three new HLA‐C alleles were identified by sequence‐based typing method (SBT) in donors for the Saudi Bone Marrow Donor Registry (SBMDR). HLA‐C*14:02:13 differs from HLA‐C*14:02:01 by a silent G to A substitution at nucleotide position 400 in exon 2, where lysine at position 66 remains unchanged. HLA‐C*15:72 differs from HLA‐C*15:22 by a nonsynonymous C to A substitution at nucleotide position 796 in exon 3, resulting in an amino acid change from phenylalanine to leucine at position 116. HLA‐C*15:74 differs from HLA‐C*15:08 by a nonsynonymous C to T substitution at nucleotide position 914 in exon 3, resulting in an amino acid change from arginine to tryptophan at position 156.